2015
DOI: 10.1519/jsc.0000000000000626
|View full text |Cite
|
Sign up to set email alerts
|

The Power Output and Sprinting Performance of Young Swimmers

Abstract: The aim of this article was to compare swimming power output between boys and girls and to model the relationship between swimming power output and sprinting performance in young swimmers. One hundred young swimmers (49 boys and 51 girls, aged between 11 and 13 years) underwent a test battery including anthropometrics (body mass, height, arm span [AS], and trunk transverse surface area), kinematic and efficiency (velocity, stroke frequency, stroke length, speed fluctuation, normalized speed fluctuation, stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 27 publications
2
39
0
1
Order By: Relevance
“…Although the body mass and height measurements for the 12-year-old swimmers in the studies by Cochrane et al (2015) and Ricardo (2011) were higher than those found in our study, the mass and height results in two other studies are consistent with our findings (Barbosa et al, 2015;Geladas et al, 2005;Marinho et al, 2009). However, the BFR measurements for the male swimmers in the current study was lower than that of a similar age group in the study by Cochrane et al (2015).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the body mass and height measurements for the 12-year-old swimmers in the studies by Cochrane et al (2015) and Ricardo (2011) were higher than those found in our study, the mass and height results in two other studies are consistent with our findings (Barbosa et al, 2015;Geladas et al, 2005;Marinho et al, 2009). However, the BFR measurements for the male swimmers in the current study was lower than that of a similar age group in the study by Cochrane et al (2015).…”
Section: Discussionsupporting
confidence: 87%
“…Although performance and success in elite swimmers depend on various factors, physical parameters (i.e., body height, body mass and somatotype characteristics) are also determinants of swimming performance. In previous studies, physical properties, anthropometric characteristics and some of the strength parameters of swimmers were identified (Cochrane et al, 2015;Richardson, Beerman, Heiss, 2000), and the correlations between these parameters and swimming performance were investigated (Barbosa, Morais, Marques, Costa, & Marinho, 2015;Girold, Calmels, Maurin, Milhau, & Chatard, 2006;Kukolj, Ropret, Ugarkovic, & Jaric, 1999). Critical swimming speed (V crit ) is typically used as a determinant of swimming performance in the literature (Wakayoshi et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropometrics, hydrodynamics, kinematics and efficiency are highly related to young swimmers' performance (Barbosa et al, 2015;Morais et al, 2012;Strzala et al, 2015). Anthropometric features are strongly related to technical parameters (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, the S&C training design should be specific for the requirements of the concerned sport. In swimming, performance is highly dependent on strength and muscular power (5,11,14,21), being the ability to exert force in the water a decisive factor, specifically in short distances (18,25). Consequently, swimming coaches traditionally apply dry-land S&C programs in their training sessions (1,3,9,23) even if consensus on the specific benefits to a swimmer's performance has not yet been clarified in literature (11,23,27,33).…”
mentioning
confidence: 99%